Estimation of Attenuation Coefficient Values Using Remote Sensing and Its Relationship With Shallow Water Depth - Anggi Tiarasani; Vincentius Paulus Siregar; Jonson Lumban Gaol (Journal of Applied Geospatial Information, 2023)
In ocean remote sensing, the intensity of light entering the water column decreases exponentially with increasing depth due to scattering and particle absorption in the water column. This process of decreasing light intensity is called attenuation. Attenuation is a limiting factor in detecting objects in the water column and seafloor using remote sensing, which relies on light intensity. The attenuation coefficient (Kd) is an important optical property of seawater as it provides information about water clarity and the level of light attenuation. This study aims to analyze the estimation of the attenuation coefficient values and their variability using in-situ measurements and Sentinel-2 level 2A data in Karang Lebar, Pulau Panggang, and Pulau Air, in the Seribu Islands Regency, North Jakarta. We tested several algorithms to estimate the attenuation coefficient values. The research results show that the in-situ Kd and the estimated model values have a good correlation (r = 0.75-0.86). The distribution of attenuation coefficient values in the shallow waters of the study area ranges from 0.06 to 0.18m-1. The accuracy of estimating shallow water depth at the study sites was best represented by R2 and RMSE values in the range of 0-5m with an attenuation coefficient of 0.06-0.11m-1. Keywords: Diffuse Attenuation Coefficient, Remote Sensing, Sentinel-2 Imagery, Algorithm.